Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration - Rodriguez-Calcerrada, Jesus; Limousin, Jean-Marc; Martin-StPaul, Nicolas K; Jaeger, Carsten; Rambal, Serge (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020
Keywords: carbon budget; ecosystem respiration; leaf life span; resource remobilization; soluble sugars; temperature sensitivity